1998
DOI: 10.1055/s-2006-957417
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Naphthoquinones fromNepenthes thorelii

Abstract: Roots of Nepenthes thorelii yielded plumbagin, 2-methylnaphthazarin, octadecyl caffeate, isoshinanolone, and droserone. In addition, seven derivatives were prepared from plumbagin. Each of these natural and semisynthetic compounds was evaluated for in vitro antimalarial potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 17 publications
0
81
0
Order By: Relevance
“…antimalarial (Likhitwitayawuid et al 1998), antimicrobial (Didry et al 1994), anticancer (Parimala and Sachdanandam, 1993), cardiotonic (Itoigawa et al 1991) and antifertilityaction (Bhargava, 1984). At present, the most exploited source of plumbagin are the roots of Plumbago spp.…”
mentioning
confidence: 99%
“…antimalarial (Likhitwitayawuid et al 1998), antimicrobial (Didry et al 1994), anticancer (Parimala and Sachdanandam, 1993), cardiotonic (Itoigawa et al 1991) and antifertilityaction (Bhargava, 1984). At present, the most exploited source of plumbagin are the roots of Plumbago spp.…”
mentioning
confidence: 99%
“…Plumbagin, droserone, hydroxydroserone, and other four new quinones including nepenthone-A, nepenthone-B, nepenthone-C, and nepenthone-E were obtained from Nepenthes rafflesiana roots, while the fifth quinone, nepenthone-D was identified [30]. Likhitwitayawuid et al isolated 2-methylnaphthazarin, droserone, isoshinanolone, octadecylcaffeate, and plumbagin from the roots of Nepenthes thorelii [20] [22]. The compounds epishinanolone, isoshinanolone, kaempferol, plumbagin, quercetin, and shinanolone were successfully isolated from the leaves of N. gracilis by Aung et al [26].…”
Section: Sanusi Et Almentioning
confidence: 99%
“…have been utilized in traditional medicine system to treat and control different ailments including gastrointestinal discomfort, such as dysentery, stomachache, and bed-wetting among others [17]. A wide range of phytochemicals were identified and isolated from different species of Nepenthes [18][19][20][21][22]. The previous researches showed that Nepenthes spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is a naturally occurring yellow pigment mainly isolated from the genus Plumbago (Plumbaginaceae), which have especially been attracted much attention as a drug candidate. It has been shown to have various pharmacologic activities against cancer, 7) fungi, 8) malaria, 9) insects, 10) and Helicobacter pylori. 11) In addition, PL is capable of inhibiting cell proliferation by inducing autophagic cell death.…”
mentioning
confidence: 99%